The Geography of Solar Photovoltaics (PV) and a New Low Carbon Urban Transition Theory - Newton, P.; Newman, Peter (Adver, SUSTDE, 2013)
This paper examines the early phases of a 21st century energy transition that involves distributed generation technologies employing low or zero carbon emission power sources and their take-up within Australia, with particular reference to the major cities and solar photovoltaics (PV). This transition is occurring in a nation with significant path dependency to overcome in relation to fossil fuel use. Tracking the diffusion of solar PV technology within Australia over the past decade provides a basis for assessing those factors underpinning its exponential growth and its associated geography of diffusion. Positive evidence that there are pathways for cities to decarbonise is apparent but there appear to be different pathways for different city forms with lower density suburban are as showing the biggest take-up of household-based energy technologies. This suggests a model for the low carbon urban transition involving combinations of simple technological changes and harder structural changes, depending upon which parts of the urban fabric are in focus. This is being called a New Low Carbon Urban Transition Theory.